Identifikasi Potensi Enzim Lipase dan Selulase pada Sampah Kulit Buah Hasil Fermentasi - La Ode Sumarlin; Dikdik Mulyadi; . Suryatna; Yoga Asmara (Institut Pertanian Bogor, 2013)
Fermentation is one of bioconversion to produce profitable anaerobic microbes and to produce various enzymes. Lipases and cellulases are widely used enzymes so far. Cellulases play an important role in bioconversion of organic waste cellulosic materials to glucose, single cell proteins, animal feed, and ethanol. Lipases can also degrade fatty ester bond. Therefore, both enzymes are potential to be used in industry as well as in households. Fermentation of fruit peel waste is an attempt to produce cellulase and lipase that can be carried out in a simple way. Cellulase as says was performed using DNS (3.5-dinitrosalicylic acid) and acid-base titration for analysis of lipase using cooking oil as the substrate. The results showed that the highest cellulase activity was obtained from watermelon rind mixed with citrus fruit peel of 0.036 U/mL, and mixed of banana peel and citrus fruit, which was 0.035 U/mL. The optimum lipase activity was at 30 oC, pH 7, and reaction time of 60 minutes. The highest lipase activity (1.36 U/mL) was obtained from mixture of watermelon and orange rind. Thus, the fruit peel waste is potential to produce cellulase and lipase by fermentation .